The Effect of Women Proportion in Board of Commissioners, Board of Directors, and Audit Committee on Earnings Management - Ni Made Pradnya Indira Swari; Ni Made Dwi Ratnadi; I Nyoman Wijana Asmara Putra; Ni Putu Sri Harta Mimba (Eduvest - Journal of Universal Studies, 2026)
Earnings management remains a relevant research issue due to the separation of ownership and control, which creates agency conflicts. Earnings management can be reduced by implementing effective corporate governance. One of its aspects is governance structure, which includes the board of commissioners, board of directors, and audit committee. This study aims to examine the effect of the proportion of women on the board of commissioners, board of directors, and audit committee on earnings management. The sample includes 363 non-financial companies listed on the Indonesia Stock Exchange, with an observation period from 2016 to 2023; these were selected using purposive sampling and analyzed through panel data regression. This study shows that the proportion of women on the board of directors and audit committee has a negative effect on earnings management, while the proportion of women on the board of commissioners does not affect earnings management. The presence of women comprising at least 35% on the combined board of directors and audit committee negatively affects earnings management. However, this study does not find any significant effect of the presence of women comprising at least 35% in a single position or in combined positions on earnings management. These findings provide practical implications for company management to enhance women's representation, especially on the board of directors and audit committee, thereby reducing the likelihood of earnings management.